Toxicity Studies of Cardiac-Targeting Peptide Reveal a Robust Safety Profile - Daniella A. Sahagun; Jack B. Lopuszynski; Kyle S. Feldman; Nicholas Pogodzinski; Maliha Zahid (MDPI AG, 2024)
Targeted delivery of therapeutics specifically to cardiomyocytes would open up new frontiers for common conditions like heart failure. Our prior work using a phage display methodology identified a 12-amino-acid-long peptide that selectively targets cardiomyocytes after an intravenous injection in as little as 5 min and was hence termed a cardiac-targeting peptide (CTP: APHLSSQYSRT). CTP has been used to deliver imaging agents, small drug molecules, photosensitizing nanoparticles, exosomes, and even miRNA to cardiomyocytes. As a natural extension to the development of CTP as a clinically viable cardiac vector, we now present toxicity studies performed with the peptide. In vitro viability studies were performed in a human left ventricular myocyte cell line with 10 µM of Cyanine-5.5-labeled CTP (CTP-Cy5.5). In vitro ion channel profiles were completed for CTP followed by extensive studies in stably transfected cell lines for several GPCR-coupled receptors. Positive data for GPCR-coupled receptors were interrogated further with RT-qPCRs performed on mouse heart tissue. In vivo studies consisted of pre- and post-blood pressure monitoring acutely after a single CTP (10 mg/Kg) injection. Further in vivo toxicity studies consisted of injecting CTP (150 µg/Kg) in 60, 6-week-old, wild-type CD1, male/female mice (1:1), with cohorts of mice euthanized on days 0, 1, 2, 7, and 14 with inhalational CO2, followed by blood collection via cardiac puncture, complete blood count analysis, metabolic profiling, and finally, liver, renal, and thyroid studies. Lastly, mouse cardiac MRI was performed immediately before and after CTP (150 µg/Kg) injection to assess changes in cardiac size or function. Human left ventricular cardiomyocytes showed no decrease in viability after a 30 min incubation with CTP-Cy5.5. No significant activation or inhibition of any of seventy-eight protein channels was observed other than OPRM1 and COX2 at the highest tested concentration, neither of which were expressed in mouse heart tissue as assessed using RT-qPCR. CTP (10 mg/Kg) injections led to no change in blood pressure. Blood counts and chemistries showed no evidence of significant hematological, hepatic, or renal toxicities. Lastly, there was no difference in cardiac function, size, or mass acutely in response to CTP injections. Our studies with CTP showed no activation or inhibition of GPCR-associated receptors in vitro. We found no signals indicative of toxicity in vivo. Most importantly, cardiac functions remained unchanged acutely in response to CTP uptake. Further studies using good laboratory practices are needed with prolonged, chronic administration of CTP conjugated to a specific cargo of choice before human studies can be contemplated.